2018
DOI: 10.1137/17m1160094
|View full text |Cite
|
Sign up to set email alerts
|

Doubly Exponentially Many Ingleton Matroids

Abstract: A matroid is Ingleton if all quadruples of subsets of its ground set satisfy Ingleton's inequality. In particular, representable matroids are Ingleton. We show that the number of Ingleton matroids on ground set [n] is doubly exponential in n; it follows that almost all Ingleton matroids are non-representable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…1.1. First, we prove in Theorem 3.14 an interesting consequence of the results by Nelson and van der Pol [45]. Namely, every almost entropic sparse paving matroid must satisfy Ingleton inequality.…”
Section: Our Resultsmentioning
confidence: 74%
See 3 more Smart Citations
“…1.1. First, we prove in Theorem 3.14 an interesting consequence of the results by Nelson and van der Pol [45]. Namely, every almost entropic sparse paving matroid must satisfy Ingleton inequality.…”
Section: Our Resultsmentioning
confidence: 74%
“…In addition, by using the improved linear programming technique, we find new lower bounds on the information ratio of secret sharing schemes for several matroid ports. By combining our bounds for matroids on eight points with the results in [45], we present in Theorem 5.1 lower bounds that apply to every sparse paving matroid that does not satisfy Ingleton inequality. We found a lower bound on the information ratio of linear secret sharing schemes for the ports of the tic-tac-toe matroid and some of the aforementioned 171 related matroids.…”
Section: Our Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This motivates the following definition. In [23] it was shown that Vámos-like matroids violate the Ingleton inequalities. Mayhew and Royle show that among the matroids on eight elements [21], there are 44 non-representable matroids and 39 of them are Vámos-like.…”
Section: Number Of Pairs (E V) For Whichmentioning
confidence: 99%